2012
DOI: 10.2298/soc1201123h
|View full text |Cite
|
Sign up to set email alerts
|

Dispersed settlement in detached houses: Attitudes over the residential space consumption in Slovenia

Abstract: Public opinion surveys investigating the levels of environmental awareness target the most diverse aspects of environment pollution, but they rarely examine people's attitudes to the ways and forms in which space itself is used or consumed, especially in the context of residential or settlement patterns. This article analyses the connection between the prevailing long-term value orientations about residential preferences in Slovenia, which we associate with an ideology of “anti-urbanism”, and the resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Namely, it has already been shown that a great part of agricultural research gets published outside agricultural categories (Bartol et al, 2016). At the same time, we also assume that the agricultural countryside is changing along with other trends in nature and society, such as the intertwining of urban and rural, when non-productive aspects already prevail in relation to rurality, being study subjects of other disciplines (Hocevar, 2012).…”
Section: Aimsmentioning
confidence: 99%
“…Namely, it has already been shown that a great part of agricultural research gets published outside agricultural categories (Bartol et al, 2016). At the same time, we also assume that the agricultural countryside is changing along with other trends in nature and society, such as the intertwining of urban and rural, when non-productive aspects already prevail in relation to rurality, being study subjects of other disciplines (Hocevar, 2012).…”
Section: Aimsmentioning
confidence: 99%
“…The prevalence of dispersed settlements in an agricultural landscape in Ireland is highlighted by Environmental Protection Agency (2008). Dispersed settlements -tanye -were studied in the Hungarian lowlands by Kovács and Farkas (2011), dispersed and decentralized settlements in Slovenia were analyzed by Černe (2004) and by Hočevar (2012), in the eastern part of the Balkan Peninsula by Frolec (1980), in southern Spain by Amate et al (2016). Bodzak andKiełczewska-Zaleska (1973-1977) compiled a map of dispersed settlement in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…Self-evident association of the countryside depending (only) on agricultural production in a narrower sense and where such production defines the rural way of life is no longer appropriate (Hočevar, 2012;Uršič and Hočevar, 2007;Mavri and Černič-Istenič, 2014;Schroeder, 2016).…”
Section: Introductionmentioning
confidence: 99%